2021
DOI: 10.1002/jgh3.12585
|View full text |Cite
|
Sign up to set email alerts
|

Systemic quinolones and risk of acute liver failure I: Analysis of data from the US FDA adverse event reporting system

Abstract: Background and Aim Quinolones are a potent and globally popular group of antibiotics that are used to treat a wide range of infections. Some case reports have raised concern about their possible association with acute hepatic failure (AHF). Data from the US FDA Adverse Event Reporting System were evaluated for signals of AHF in association with systemically administered quinolone antibiotics. Methods AHF reports between 1969 and 2019q2, with a focus on 2010–2019q2, were analyzed. Specifically, AHF reports link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The number of patients included in the research and exposed to FQs was 7862 [ 364 ]. Additionally, recently evaluated data from the FDA Adverse Event Reporting System pointed out ciprofloxacin association with acute hepatic failure, having a marginal and a significant signal compared to the other three FQs (levofloxacin, moxifloxacin, and ofloxacin) with a weak and non-significant signal [ 365 ].…”
Section: Side-effects Of Fqs and Underlying Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of patients included in the research and exposed to FQs was 7862 [ 364 ]. Additionally, recently evaluated data from the FDA Adverse Event Reporting System pointed out ciprofloxacin association with acute hepatic failure, having a marginal and a significant signal compared to the other three FQs (levofloxacin, moxifloxacin, and ofloxacin) with a weak and non-significant signal [ 365 ].…”
Section: Side-effects Of Fqs and Underlying Mechanismsmentioning
confidence: 99%
“…Due to the potential to produce dysglycemia, FQs should be prescribed with caution in diabetic patients who have comorbidities and are on antidiabetic and/or steroid treatment [ 235 , 348 ]. In addition, before initiation of FQs therapy, the patient’s liver function would be indicated to be assessed due to the hepatotoxicity potential of FQs [ 364 , 365 , 366 , 417 ]. Additionally, the FQs should be prescribed judiciously only when no alternatives exist.…”
Section: Rational Use and Caution Of Modern Fqsmentioning
confidence: 99%
“…[5][6][7] A recent study reported ciprofl oxacin as being more likely to cause acute hepatic failure; other studies state that moxifl oxacin or levofl oxacin puts patients at higher risk. 5,[7][8][9][10] Several risk factors exist for fl uoroquinolone-associated hepatotoxicity, including age under 45 years or over 60 years, male sex, alcohol abuse, and preexisting liver impairment such as hepatitis B. 6,10 Additional risk factors include elevated transaminases or increasingly common liver diseases such as nonalcoholic fatty liver disease or nonalcoholic steatohepatitis.…”
Section: Dysglycemiamentioning
confidence: 99%
“…In the past, some FQs were withdrawn as a result of serious side-effects, including hepatotoxicity (e.g., trovafloxacin), However, the usual FQs are rarely associated with severe liver damage concerning increased transaminase levels. Ciprofloxacin is the most hepatotoxic FQ [ 58 - 61 ]. Liver damage includes hepatocellular necroses, cholestasis, and immune allergic reactions and appears to start from the first week to four weeks of treatment [ 59 , 62 ].…”
Section: Potentially Life-threatening and Disabling Adverse Effectsmentioning
confidence: 99%
“…ej., trovafloxacino), Sin embargo, las FQs habituales raramente se asocian a daño hepático grave con aumento de los niveles de transaminasas. Ciprofloxacino es la más hepatotóxica de todas las FQs [58][59][60][61]. El daño hepático incluye necrosis hepatocelular, colestasis y reacciones inmunoalérgicas y aparece a partir de la primera semana hasta las cuatro semanas de tratamiento [59,62].…”
Section: Efectos Adversos Potencialmente Mortales E Incapacitantesunclassified